Intense resistance training induces pronounced metabolic stress and impairs hypertrophic response in hind-limb muscles of rats - Guzzoni, Vinicius; Briet, Larissa; Costa, Rafaela; Souza, Rodrigo W. A. [UNESP]; Carani, Fernanda R. [UNESP]; Dal-Pai-Silva, Maeli [UNESP]; Silva, Kleiton A. S.; Cunha, Tatiana S.; Marcondes, Fernanda K. (Taylor & Francis Ltd, 2019)
Skeletal muscle hypertrophy is an exercise-induced adaptation, particularly in resistance training (RT) programs that use large volumes and low loads. However, evidence regarding the role of rest intervals on metabolic stress and muscular adaptations is inconclusive. Thus, we aimed to investigate the effects of a strenuous RT model (jump-training) on skeletal muscle adaptations and metabolic stress, considering the scarce information about RT models for rats. We hypothesized that jump-training induces metabolic stress and influences negatively the growth of soleus (SOL) and extensor digitorum longus (EDL) muscles of rats. Male Wistar rats (aged 60 days) were randomly assigned to non-trained or trained groups (n = 8/group). Trained rats performed jump-training during 5 days a week for 1, 3, or 5 weeks with 30 s of inter-set rest intervals. Forty-eight hours after the experimental period, rats were euthanized and blood samples immediately drawn to measure creatine kinase activity, lactate and corticosterone concentrations. Muscle weight-to-body weight ratio (MW/BW), cross-sectional area (CSA) and myosin heavy chain (MHC) isoform expression were determined. Higher lactate levels occurred after 20 min of training in weeks 1 and 3. Corticosterone levels were higher after 5 weeks of training. Jump-training had negative effects on hypertrophy of types-I and II muscle fibers after 5 weeks of training, as evidenced by decreased CSA and reduced muscle weight. Our results demonstrated that pronounced metabolic stress and impairment of muscle growth might take place when variables of exercise training are not appropriately manipulated. Lay summary Resistance training (RT) has been used to increase muscle mass. In this regard, training variables (intensity, volume, and frequency) must be strictly controlled in order to evoke substantial muscular fitness. This study shows that rats submitted to 5 weeks of intensive resistance jump-training - high intensity, large volume, and short rest intervals - present high levels of blood corticosterone associated with negative effects on hypertrophy of types-I and II muscle fibers.
Keywords: Corticosterone; exercise volume; jump-training; lactate; rest intervals; skeletal muscle